2015
DOI: 10.1080/15384047.2015.1056418
|View full text |Cite
|
Sign up to set email alerts
|

DecreasedSMAD4expression is associated with induction of epithelial-to-mesenchymal transition and cetuximab resistance in head and neck squamous cell carcinoma

Abstract: Epidermal growth factor receptor (EGFR) is frequently overexpressed in head and neck squamous cell carcinoma (HNSCC) and cetuximab, a monoclonal antibody targeting this receptor, is widely used to treat these patients. In the following investigation, we examined the role of SMAD4 down-regulation in mediating epithelial-to-mesenchymal transition (EMT) and cetuximab resistance in HNSCC. We determined that SMAD4 downregulation was significantly associated with increased cell motility, increased expression of vime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…SMAD4 expression was detected in 86.9% of patients, but was undetectable in 6 (4.6%) tumors (Supplemental Table 1). This is consistent with 7% of HNSCC having SMAD4 alteration via homozygous deletion, and nonsense, missense, and silent mutations resulting in complete loss, while relative downregulation of SMAD4 expression is more commonly seen in 44.8% of HNSCC based on the gene expression analysis of TCGA dataset as previously published by our group (27). Of the 6 SMAD4 negative patients, 5 patients had a tumor site other than the oropharynx and were HPV negative.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…SMAD4 expression was detected in 86.9% of patients, but was undetectable in 6 (4.6%) tumors (Supplemental Table 1). This is consistent with 7% of HNSCC having SMAD4 alteration via homozygous deletion, and nonsense, missense, and silent mutations resulting in complete loss, while relative downregulation of SMAD4 expression is more commonly seen in 44.8% of HNSCC based on the gene expression analysis of TCGA dataset as previously published by our group (27). Of the 6 SMAD4 negative patients, 5 patients had a tumor site other than the oropharynx and were HPV negative.…”
Section: Resultssupporting
confidence: 90%
“…We have previously shown that in HNSCC obtained from TCGA dataset, HPV-negative tumors are more likely to have lower SMAD4 expression than HPV-positive HNSCC (27). Furthermore, we showed that decreased SMAD4 expression induces HPV-negative tumor cells to undergo EMT and renders them resistant to the EGFR inhibitor cetuximab (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perturbation of the TGFβ pathway-including the two TGFβ superfamily receptors TGFBR2 and ACVR2A and their downstream effector, the transcription factor SMAD4-all showed phenotypes. SMAD4 loss has been shown previously to impact resistance to EGFRis (Cheng et al 2015), but how it suppresses EGFRi sensitivity is not known. Other key pathways illustrated in the screen involved proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%